Illuminating political experience : exercises on Hannah Arendt's thought - Hyvönen, Ari-Elmeri (2017)
This study focuses on our ability to meaningfully respond to political events and experience. It provides a reading of Hannah Arendt’s (1906–1975) political thought in a context informed by recent political events – such as the so called ‘Arab Spring’ of 2011 – and contemporary political theory. The dissertation consists of four articles and a summary chapter, each of which makes a separate but related contribution to the field. The study explores Arendt’s notion of political experience and its role in political thinking more broadly. It argues that while the importance of experience is often noted in the existing scholarship on Arendt, a proper exploration of its meaning is lacking. It also inquires into the contemporary relevance of her experiential thought, and seeks to identify various political and conceptual obstacles on the way to doing justice to experience. The main contributions of the study are fourfold. First, using both published and archive materials, it provides a richer description of Arendt’s notion of experience. It argues that the idea of vicarious re-experiencing of political events plays more important a role for Arendt than is usually granted. By focusing on the role of metaphoric concepts, it is also suggested that the notion of experience so understood remains provocative in the context defined by the linguistic turn. Second, the study highlights the original aspects of this understanding of experience against the background of other well-known concepts of political experience. Third, it maintains that Arendt’s emphasis on the experience-based nature of her theorizing is embodied in her choice of the essay as a key literary platform. Focusing on this genre, the thoroughly tentative nature of political thought comes to the fore. Fourth, the dissertation offers detailed analyses of ways of framing experience that have harmful effects on our ability to apprehend political events. It examines process-oriented thinking that dominates our approach to events and modern administration. In both cases, particular experiences are reduced to functions of an all-encompassing process, hence eroding important aspects of worldly experience. Additionally, the study criticizes the ascendancy of the ‘resistance’ frame in the discussion of political action. This approach, like the process frame, tends to dim aspects of political experience: practices of world-changing as a form of freedom and the related joyous affective experiences. On these grounds, the dissertation as a whole defends Arendt’s thinking as a promising attempt to embrace both the subjective and the worldly, temporally durable aspects of political experience in a way that also speaks to our most recent experiences from the Arab Spring to the emergence of ‘post-factual’ politics.